Obraz domu rodzinnego we wspomnieniach dorosłych dzieci alkoholików - Klimczak, Wioletta (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The aim of this paper is to present the image of the family house formed in the memories of adult children of alcoholics. It might contribute to a better understanding of the life situation of those persons. We will be analyzing the roles played by different family members, the characteristics and properties of the familial environment in which have grown the persons what had at least one parent addicted to alcohol. Based on the mentions, described in narrations, we will represent the image of the family house functioning in the memory of adult persons that have grown in a family with an alcohol problem. We will describe the early experiences of those person in the area of mutual relationship, behaviors and customs in their families during their childhood.
Keywords: alcoholic family; child; childhood; adult children of alcoholics